THU0205 Cardiovascular Evaluation Using Non-Invasive Imaging Methods in Patients with Ankylosing Spondylitis Before and After 12 Months of Treatment with anti-TNF Drugs. (9th June 2015) - Atzeni, F.; Gianturco, L.; Bongiovanni, S.; Colombo, D.; Talotta, R.; Sarzi-Puttini, P.; Turiel, M.
Abstract : Background: A number of studies indicate that AS is also associated with various non-atherosclerotic CV manifestations. The inflammatory processes in AS may affect different structures of the heart: the most characteristic lesions are conduction defects and aortic insufficience. Objectives: The primary aim was to evaluate left ventricular myocardial function with two- dimensional speckle tracking echocardiography (STE), in addition to conventional Doppler and tissue Doppler echocardiography, in order to detect subclinical left ventricular myocardial dysfunction in patients with AS. The secondary aim was to evaluate the effect of anti-TNF drugs on heart parameters. Methods: The study involved 30 outpatients who fulfilled the New York diagnostic criteria for AS (14 males and 16 females; mean age 53.07±10.73 years) and 30 healthy matched controls. All of the AS patients were evaluated at baseline at after 12 months of anti-TNF treatment. All patients underwent a complete physical examination and routine laboratory analysis. Disease activity was assessed by the BASDAI. CV risk profiles were assessed by means of standard electrocardiography (ECG), conventional echocardiography, carotid ultrasonography and pulse wave velocity (PWV). Two-dimensional echocardiographic images were obtained using the apical 4-chamber view at a high frame rate of 70-80 frames/s, and three cardiac cycles were stored in cine-loop format for off-line analysis using commercially available QLAB 9 software (Philips Medical System, USA) in order to assess end-systolic LV longitudinal strain (ɛ). Results: None of the patients showed any signs or symptoms of CV disease, pulmonary involvement, or any other complication. The patients' mean LVEF and E/A ratios were respectively 62.64±5.07% and 0.84±0.20%, which were not significantly different from those of the controls (63.45±6.54% and 0.90±0.22%). The results of the speckle tracking analysis were significantly different between the two groups, with global longitudinal strain deformation in the apical 4-chamber view (Long. ɛ 4c) being significantly lower in the AS patients (Long ɛ 4c %: median 19.83, IQR 16.00-24.40 vs 21.46, IQR 18.35-25.69; p <0.05). Right and left pulse wave velocity (PWV) (PWV right, m/sec: median 7.81, IQR 7.03-8.45 vs 6.86, IQR 6.42-7.99; p =0.07 and PWV left, m/sec: median 7.77, IQR 6.97-8.38 vs 6.85, IQR 6.28-7.88; p =0.06) and right and left coronary intima media thickness (cIMT) (cIMT right, mm: median 0.63, IQR 0.45-0.81 vs 0.64, IQR 0.50-0.78; p =0.06 and cIMT left, mm: median 0.63, IQR 0.46-0.80 vs 0.63, IQR 0.49-0.79; p =0.06) values were all higher in the AS patients, but the differences of cIMT were not statistically significant. Furthermore a significant improvement in Long. ɛ 4c of LV in AS patients at 12 months of the anti-TNF treatment was observed (Long. ɛ 4c %: median 19.83, IQR 16.00-24.40 vs 22.32, IQR 18.10-25.80 p <0.01), such as a minimal reduction of arterial stiffness and cIMT parameters ( p =n.s). Conclusions: LV myocardial longitudinal ɛ was impaired in AS patients in the absence of any clinical evidence of CV disease and echocardiographic evaluations negative, suggesting a myocardial alteration. Moreover, anti-TNF therapy improves heart parameters, but further studies are required. Disclosure of Interest: None declared